Complete agenesis of the infra‐renal aorta. Issue 12 (26th December 2021) - Seretis, Charalampos; Papageorgopoulou, Chrysanthi P.; Nikolakopoulos, Konstantinos M.; Tsimpoukis, Andreas L.; Papadoulas, Spyros I.
Abstract: Complete agenesis of the infra‐renal aorta is an extremely rare anatomical variant, and its presence can complicate the accurate interpretation of the aortic sonographic assessment. Abstract : Complete agenesis of the infra‐renal aorta is an extremely rare anatomical variant, and its presence can complicate the accurate interpretation of the aortic sonographic assessment.